Biofungicidal potential of selected plant extracts against fruit rot pathogens of banana, tomato and mango - Abd Murad, Nur Baiti (2022)
Fruit rot caused by several fungal pathogens can be considered as a threat to economic loss due to quality defect and quantity loss, besides constitute health risk to the consumers due to mycotoxin contamination produced by the pathogens. Frequent and unselective use of fungicide to control the pathogens has ended up to resistant development of the pathogens and increase toxic accumulation in fruits. Previous studies reported that plant extracts might contain variety of bioactive constituents that able to control the pathogen’s growth. Hence, the aims of this study were to screen antifungal activity of selected plant extracts against Fusarium oxysporum, Fusarium proliferatum, Colletotrichum gloeosporioides and Lasiodiplodia theobromae under in vitro condition, to examine morphological and cytological changes of the pathogens treated with selected plant extracts using scanning (SEM) and transmission (TEM) electron microscope, to evaluate the efficacy of the selected plant extracts against fruit rot disease and to identify phytochemical constituents of the selected plant extracts using Ultra High Performance Liquid Chromatography Mass Spectrometer (UHPLC MS/MS). The plant extracts of Pilea microphylla, Peperomia pellucida, Persicaria odorata, Cymbopogon citratus, Tamarindus indica, Garcinia mangostana and Averrhoa bilimbi were prepared using different types of solvents and in vitro screening was conducted using poisoned food bioassay. Eight out of 48 plant extracts showed high significant inhibition effect against mycelial growth of F. oxysporum and F. proliferatum, while no extracts showed high significant inhibition effect against C. gloeosporioides growth and no extracts showed significant inhibition effect against L. theobromae when compared to positive controls. The eight effective extracts were further used to examine their inhibition effect on conidial germination. The results showed G. mangostana pericarp and A. bilimbi fruit ethanolic extracts significantly lowered the conidial germination of F. oxysporum (14.33%) and (20.00%), F. proliferatum (28.33%) and (39.75%), C. gloeosporioides (14.67%) and (20.00%) and L. theobromae (18.89%) and (28.57%) when compared to the controls. Shrivelled mycelia were observed via SEM on pathogens treated with both plant extracts indicating morphological changes were occurred in the cell compared to the controls in which the mycelia were in normal form. Alterations in hyphae cellular structures of the treated pathogens were observed via TEM, indicating cytological changes occurred in the cell membrane when compared to the controls in which the hyphae cells were in normal form. The selected plant extracts at different concentrations showed varied degrees in disease severity reduction percentages against all pathogens, especially to F. oxysporum and F. proliferatum that were inoculated on different type of fruits; banana, tomato and mango. G. mangostana pericarp ethanolic extract at concentration of 100 mg/mL exhibited the equivalent efficacy in supressing fruit rot disease in both banana and tomato fruits, while A. bilimbi fruit ethanolic extract at concentration of 100 mg/mL showed significant reduction in fruit rot development on mango when compared to fungicide carbendazim. Significant changes on fruit quality of banana and tomato were displayed by the treatment of G. mangostana pericarp ethanolic extract, while A. bilimbi fruit ethanolic extract treatment showed significant changes in fruit quality of mango, when compared to the control fruits. Identification of phytochemical constituents was exhibited the presence of some of vital component groups which contributed to the antifungal activity of the extracts. UHPLC MS/MS spectral analysis displayed 50 metabolites in the negative ion mode, while 68 metabolites were identified in the positive ion mode of G. mangostana pericarp ethanolic extractcor respondingly. Meanwhile, 59 metabolites were tentatively identified in the negativeion mode, whereas 109 metabolites were identified in the positive ion mode of A. bilimbi fruit ethanolic extract respectively. The equivalent and greater effect of G. mangostana pericarp and A. bilimbi fruit ethanolic extracts when compared to fungicide carbendazim was due to the presence of phytochemical compounds that possessed antifungal properties. This innovation has potential to be applied as an eco-friendly and gentle approach to control fruit rot disease.